(untitled) (Sains Humanika, 2015)
There is some research investigating toward e-commerce adoption around the world. However, the research of e-commerce adoption in developing countries and small business are not as much as large companies. For this reason, this study investigates e-commerce adoption in small business and developing country such in Indonesian case and small travel Enterprises (STEs). The research study focuses on electronic travel (e-travel) adoption as a subdivision of electronic commerce (e-commerce) in Padang, West Sumatra Province. The research framework presents measurement indicators including operational and final performance of STEs in adopting e-travel. The research would be undertaken descriptively using purposive sampling technique is used for 5- STEs as the non-adoption e-travel. Thus they would be assisted generating the company’s website and be indentified the performance measurement for each STE after six month’s operations. The performance measurements of e-travel adoption involve operational and final performance. Operational performance is measured by operation activities, daily processing and resources used. Final performance is measured by market share, sales, net profit, growth, Return on Investment (ROI), and extend to global market. The measurement result would give an initial illustration during e-travel adoption by STEs in Indonesia. Further study would be investigated empirically the final performance of e-travel adoption among STEs.